Engineered silk-dressing for acceleratedwound healing: biocompatibility and efficacy studies - Deshpande, Rucha; Pillai, Lakshmi R.; Sayyad, Raeesa; Shukla, Swati; Nisal, Anuya; Venugopalan, Premnath (Macromolecular Bioscience, 2025)
Advanced wound care dressings are essential for improving clinical outcomes. The present study investigates the wound management potential of a unique dressing fabricated from silk proteins. The dressing was characterized for its physical and structural properties, including surface texture, porosity, fluid absorption capacity, and moisture vapor transmission rate. These parameters have been found to be critical for optimal wound healing. In vivo full thickness wound healing studies in a rat model validated the efficacy of the Silk-dressing compared to conventional cotton gauze and commercial polyurethane foam dressings. Histopathological analysis confirmed improved re-epithelialization, collagen deposition, angiogenesis, and formation of secondary follicles. Key advantages of Silk-dressing included non-adherence, absorption of exudate, maintenance of optimal moisture at wound site and acceleratedwound closure. Biocompatibility studies were also conducted in accordance with ISO 10993 guidelines, demonstrating no cytotoxicity, irritation, sensitization, or pyrogenicity. These findings highlight the potential of this uniquely designed Silk-dressing as a superior alternative for wound management, with a potential to improve clinical outcomes.
Keywords: Biocompatibility; biopolymer; ISO 10993; Silk protein; wound Healing